2013
DOI: 10.1186/1476-511x-12-187
|View full text |Cite
|
Sign up to set email alerts
|

Association study of angiotensin converting enzyme gene polymorphism with elderly diabetic hypertension and lipids levels

Abstract: ObjectiveTo investigate the relationship between angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism and diabetic essential hypertension in elderly population.MethodsPolymerase chain reaction (PCR) technique was used in 260 elderly normal control patients, 205 elderly hypertensive patients and 138 elderly diabetic hypertensive patients to detect the I/D polymorphism in ACE gene.ResultsDD genotype frequency (0.352) and D allele frequency (0.543) in elderly hypertensive patients were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
2
15
0
2
Order By: Relevance
“…Epidemiological studies show that various genetic and environmental factors are involved in the pathogenesis of Hypertension. ACE is the key enzyme in the Renin-Angiotensin system, which can catalyze the conversion of Angiotensin-I to Angiotensin-II [22,24,41].The ACE gene is located in chromosome 17q23 and contains 26 exons and 25 introns with a total length of 21 kb. The Insertion/Deletion (I/D) polymorphisms are defined according to presence or absence of the 287 bp fragment in intron 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies show that various genetic and environmental factors are involved in the pathogenesis of Hypertension. ACE is the key enzyme in the Renin-Angiotensin system, which can catalyze the conversion of Angiotensin-I to Angiotensin-II [22,24,41].The ACE gene is located in chromosome 17q23 and contains 26 exons and 25 introns with a total length of 21 kb. The Insertion/Deletion (I/D) polymorphisms are defined according to presence or absence of the 287 bp fragment in intron 16.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that polymorphisms of certain genes related to metabolism, including that of ACE, are also associated with the onset and development of Type 2-Diabetes [22, 24 -25]. There is a 287 bp DNA fragment insertion (I) and /or deletion(D) polymorphism in the intron 16 of ACE gene [22,26], which was recently studied [27][28][29][30][31] …”
Section: Introductionmentioning
confidence: 99%
“…Apart from being a very potent vasoconstrictor, through the induction of proteolysis of bradykinin 2, Angiotensin II participates in the regulation of glucose and insulin levels. In diabetes, the hyperglycemia‐induced increase of angiotensin II levels has been found to induce oxidative stress, inflammation, damage of endothelial cells, and thrombosis . The I/D polymorphism of the ACE gene is classified into three types—II, ID, and DD—and is defined by an insertion (I allele) or deletion (D allele) of a 287 base pair Alu sequence in intron 16 .…”
Section: Genetic Markers Of Diabetic Neuropathy Developmentmentioning
confidence: 99%
“…Previous studies commonly included young adult populations to investigate this topic and have found a significant association between ACE I/D gene polymorphism and hypertension, but our results did not confirm this association in the studied elderly population. Notwithstanding, recent studies including older adult populations have shown a greater prevalence of ID and DD genotypes (ie, presence of the D allele) among patients with hypertension …”
Section: Discussionmentioning
confidence: 93%
“…Notwithstanding, recent studies including older adult populations have shown a greater prevalence of ID and DD genotypes (ie, presence of the D allele) among patients with hypertension. 35,36 Indeed, the presence of the D allele is associated with high plasma concentrations of ACE, 37 leading to an increased peripheral vascular resistance, loss of arterial elasticity, and elevated BP. 14…”
Section: Discussionmentioning
confidence: 99%